ANALISA PERBANDINGAN DALAM RANGKA PEMILIHAN BEBERAPA IP UPSTREAM PROVIDER DI PT. INDOSAT - Yuli Anwar; Dahlar . (Jurnal Ilmiah Binaniaga, 2008)
Abstract. One of the advances in information technology that now has changed the outlook and human life, business process and business strategy of an institution is the internet. The internet is a very large networks that connected to computers and serves throughout the world in one centralized network. With the internet we can access data and information anytime and anywhere.    As one provider of high-speed data communications services and the pioneer of the internet network service provider in Indonesia that provides integrated services, as well as one of the pioneer development of internet services that provide extensive services in the building and apply it throughout Indonesia. Indosat ready to seize opportunities for sustainable growth of business spectrum are still sprawling Indonesia.    Therefore, Indosat continues to focus on the development of increased efforts to provide the best service for customers of Indosat. Indosat will continue to develop and expand network coverage and a larger investment that the company will achieve excellence in the field of integrated telecommunications services.    Ranking by region of the IP Providers can be seen by grouping IP Providers, and management over IP Providers prefer to choose providers based on where it orginates as an example for the region of the U.S if it will be preferred providers that come from U.S. providers.With the commencement of the internet network optimization start early in 2008 with the selection of the appropriate IP Upstream Provider criteria, it is up to date according to data obtained from Indosat, seen any significant changes to the cost of purchasing capacity of the IP Upstream.    Based on the data obtained that until Q3 or September 2008, the number of IP Upstream Providers that previously there were 20 to 10 IP Upstream Provider, IP Transit Price total decrease of 11% to the price of IP Transit Price / Mbps there is a decrease of 78%, while from the capacity bandwith an increase of 301% capacity from 2008.